EDUKASI PENCEGAHAN STUNTING MELALUI SOSIALISASI PENTINGNYA NUTRISI IKAN DI DESA PERSIAPAN AWANG, LOMBOK TENGAH - Diniariwisan, Damai; Junaidi, Muhammad; Dwiyanti, Septiana; Diniarti, Nanda; Sumsanto, Muhammad; Diamahesa, Wastu Ayu; Larasati, Chandrika Eka; Mulyani, Laily Fitriani (Jurnal Pepadu, 2024)
Stunting in children under five years old is the most common nutritional problem in Indonesia, namely around 30.8%. Stunting is characterized by a body height that is shorter than the average height of children in the same age. The high number cases of stunted toddlers has become a concern for the Government, where various efforts have been made to reduce the stunting rate, one of which is through socialization. Based on the results of location survey, Awang Preparation Village, in Central Lombok Regency has never received stunting socialization, so there are still many people who don't know about stunting and the benefits of fish nutrition to prevent stunting itself. The method for this activity is socialization which consists of 2 stages, namely 1) preparation which includes material preparation and timing, and 2) implementation, namely the ongoing socialization activity. This activity was attended by a total of 29 participants from among women consisting of housewives and teenagers. The results obtained after the socialization activities were that participants had a better understanding of what stunting is and how to prevent it. Apart from that, participants also know what the nutritional content of fish is so that it can be a solution to prevent stunting. Increasing maternal knowledge and awareness of the dangers of stunting can be an early indicator of a decline in stunting cases.